2008
DOI: 10.25011/cim.v31i6.4918
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic diabetic mesenchymal stem cells transplantation in streptozotocin-induced diabetic rat

Abstract: Background: Bone marrow-derived mesenchymal stem cells (BM-MSCs) are multipotent stroma cells which can provide a potential therapy for diabetes mellitus. But the mechanism is still controversial. Also, the status of BM-MSCs under hyperglycemia is not known. In the present study, we investigated the status of BM-MSCs in experimental-diabetic rat and demonstrated the rescue of experimental diabetes by diabetic MSCs transplantation. Methods: BM-MSCs were cultured and the potential of multiple-differentiation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 34 publications
2
43
4
Order By: Relevance
“…While hess et al [51] reported marked reduction of serum glucose occur as early as 4 days after transplantation of bone marrow derived cells into STZtreated mice due to stimulation of endogenous cells to proliferate and produce insulin. In accordance with our study, some evidences reported that single infusion of MSCs decrease blood glucose in STZ diabetic rats [52], [53]. Dong et al [52] reported that MSCs homed to pancreas of recipient rats and transdifferentiated into insulin-producing cells.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…While hess et al [51] reported marked reduction of serum glucose occur as early as 4 days after transplantation of bone marrow derived cells into STZtreated mice due to stimulation of endogenous cells to proliferate and produce insulin. In accordance with our study, some evidences reported that single infusion of MSCs decrease blood glucose in STZ diabetic rats [52], [53]. Dong et al [52] reported that MSCs homed to pancreas of recipient rats and transdifferentiated into insulin-producing cells.…”
Section: Discussionsupporting
confidence: 75%
“…In accordance with our study, some evidences reported that single infusion of MSCs decrease blood glucose in STZ diabetic rats [52], [53]. Dong et al [52] reported that MSCs homed to pancreas of recipient rats and transdifferentiated into insulin-producing cells.…”
Section: Discussionsupporting
confidence: 75%
“…MSCs have been shown to be capable of "homing" to the damaged area of the body and replacing injured cells (Vija et al, 2009). Xu et al reported that MSC transplantation could help in recovery of the pancreas that was injured by injection of STZ or attacked by T cells, through paracrine mechanisms (Xu et al, 2008). In fact, MSCs can secrete a variety of cytokines, growth factors, and stimulating factors that come in contact with the surrounding cells.…”
Section: Discussionmentioning
confidence: 99%
“…This positive paracrine effect on the damaged beta cells could help to protect these cells from apoptosis and to promote the proliferation of intrinsic pancreatic progenitor cells. This effect is also related to angiogenesis, cell protection, anti-inflammatory activities, promotion of mitosis, and apoptosis resistance (Bell et al, 2012;Gao et al, 2014;Xu et al, 2008). Furthermore, MSCs can trans-differentiate into insulin-producing cells (IPCs) in vivo in a suitable microenvironment (Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation